2012
DOI: 10.1371/journal.pone.0053335
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Persistence and Relapses Questions on the Treatment Strategies of Enterococcus Infections of Prosthetic Valves

Abstract: We used amplification of the 16S rRNA gene followed by sequencing to evaluate the persistence of bacterial DNA in explanted heart valve tissue as part of the routine work of a clinical microbiology laboratory, and we analyzed the role of this persistence in the relapses observed in our center. We enrolled 286 patients treated for infective endocarditis (IE) who had valve replacement surgery and were diagnosed according to the modified Duke’s criteria described by Li et al. from a total of 579 IE cases treated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Studies suggested a higher frequency of relapse among non-operated prosthetic valve-related-endocarditis: 11% to 17.4%, consistent with our 12.8% rate [ 33 , 34 ]. Our data suggest that the presence of a prosthetic valve is not associated with relapse, whereas surgery seems to be the best way to prevent it.…”
Section: Discussionsupporting
confidence: 91%
“…Studies suggested a higher frequency of relapse among non-operated prosthetic valve-related-endocarditis: 11% to 17.4%, consistent with our 12.8% rate [ 33 , 34 ]. Our data suggest that the presence of a prosthetic valve is not associated with relapse, whereas surgery seems to be the best way to prevent it.…”
Section: Discussionsupporting
confidence: 91%
“…DNA from Streptococcus spp. seems to be particularly persistent in clinical samples compared to DNA from others bacte- rial species despite appropriate antibiotherapy [36,37]. As an example, DNA can persist for as long as 7 years after the infectious episode in a cardiac valve in a patient with endocarditis.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, when a WD patient begins antibiotherapy, PCR detection becomes negative soon after treatment. This result is the opposite of the slow clearance of bacterial DNA observed during treatment of infective endocarditis 17 . In contrast, discontinuing treatment for WD is associated quickly with relapse and a positive PCR-based diagnosis 18 .…”
mentioning
confidence: 86%